Diabetes risk status and meeting the US physical activity recommendations in reproductive‐aged women: 2011, 2013, 2015 and 2017 Behavioral Risk Factor Surveillance System. Issue 8 (9th June 2022) - Rand, Bethany G.; Ehrlich, Samantha F.; Johnson, Tammie M.; Churilla, James R.
Abstract: Background: Women at increased risk for type 2 diabetes, due to recognized prediabetes (PD) or previous gestational diabetes (GD), stand to benefit from meeting U.S. physical activity (PA) recommendations. This study examined the association of diabetes risk status with meeting aerobic activity (AA), muscle strengthening activity (MSA) and both recommendations. Methods: Non‐pregnant women, 18–44, free of recognized diabetes, who participated in the 2011, 2013, 2015, or 2017 U.S. Behavioral Risk Factor Surveillance System survey ( N  = 211, 114) were categorized as no diabetes (ND; n  = 202, 766, referent) versus at‐risk for diabetes (RD; n  = 8348). Logistic regression models generated odds ratios (ORs) and 95% confidence intervals (95% CIs), adjusted for demographics and BMI. Tests for multiplicative interactions were performed for BMI category and race and ethnicity. Results: There were lower odds of meeting AA, MSA and both recommendations in the RD group (referent = ND; OR 0.95 [5% CI 0.78, 0.97], 0.83 [95% CI 0.91, 0.98] and 0.87 [95% CI 0.78, 0.97], respectively). Effect modification by BMI category was detected for models assessing MSA ( p  = 0.10), both ( p  = 0.07) and neither recommendation ( p  = 0.005), but not for AA. Among those with a BMI in the healthy and overweight groups, RD had decreased odds of meeting MSA recommendations (referent = ND; 0.69 [95% CI 0.58, 0.81] and 0.78 [95% CI 0.65, 0.93], respectively); among the healthy BMI, RD had 24% decreased odds of meeting both recommendations (referent = ND; 95% CI 0.63, 0.91). There was no difference in meeting PA recommendations among groups in the obese category, but the increased odds of meeting the AA recommendation among the RD group were approaching significance (referent = ND; [95% CI 1.00, 1.29], p  = 0.06]. Conclusion: Reproductive‐aged women with previous GD or recognized PD stand to benefit from increasing PA, especially MSA, the least often met recommendation.